Corporate governance, company size, and profitability: the role of corporate social responsibility as a moderator - Rahmadiani, Ulfa Siti; Ramadhan, Yanuar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Profitability is a crucial factor that requires special attention. This is due to the need for a company to remain profitable in order to maintain its survival. This research aims to determine the influence of Corporate Governance and Company Size on Profitability with Corporate Social Responsibility as A Moderating Variable. This research method is a quantitative research method in the period 2018 to 2022 there are 15 companies listed on the IDX which are used as population. The sampling technique in this study used purposive sampling with the criteria that the company publishes annual reports every year and the company is listed on the IDX from 2018 to 2022. After selecting the sample, the population of 15 companies obtained the company data used, namely 14 companies and 70 data which will be processed with panel data regression with statistical software. The research results show that the audit committee, independent commissioner and company size have a positive and significant effect on company profitability, CSR is able to positively moderate the influence of independent commissioners on company profitability. and CSR is unable to moderate the influence of the audit committee and company size on company profitability.